2006
DOI: 10.1007/s10620-006-3127-x
|View full text |Cite
|
Sign up to set email alerts
|

Less Irritative Action of Wine and Japanese Sake in Rat Stomachs: A Comparative Study with Ethanol

Abstract: The ingestion of alcohol, especially in excess, causes acute gastric lesions and gastritis in humans, yet the mucosal irritative action of alcoholic beverages remains largely unknown. We examined the mucosal irritative action of whiskey, wine and Japanese sake in the rat stomach both ex vivo and in vitro, in comparison with ethanol. Under urethane anesthesia, a rat stomach was mounted in an ex vivo chamber, then superfused with saline, and the transmucosal potential difference (PD) was measured. After the basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…In the present study, current drinkers tended toward prevention of total tooth loss in elderly females and similar trend was observed in males. From non‐human studies, mucosal irritation caused by Japanese sake was much less pronounced than that attributable to ethanol or whisky, a result that was possibly due to the glucose concentration 24 . Japanese elderly women may also prefer sake to other kinds of alcoholic beverages.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, current drinkers tended toward prevention of total tooth loss in elderly females and similar trend was observed in males. From non‐human studies, mucosal irritation caused by Japanese sake was much less pronounced than that attributable to ethanol or whisky, a result that was possibly due to the glucose concentration 24 . Japanese elderly women may also prefer sake to other kinds of alcoholic beverages.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, a study of 8352 men aged 40 to 79 years in Japan showed that current drinkers had a significantly lower risk of having fewer than 20 teeth [ 49 ]. Another study on a Japanese population aged 60 years or above based on analyses of the national database also concluded that the crude and adjusted ORs of former and current drinkers were both < 1 [ 12 ], and the authors explained that it was possibly due to the much less pronounced mucosal irritation caused by Japanese sake than by ethanol or whiskey [ 50 ]. In the current study, regardless of whether we limited the alcohol category to “very strong liquor (≥ 38%)” or alcohol in general, the results were not significant in either sex.…”
Section: Discussionmentioning
confidence: 99%
“…Występujące w napojach alkoholowych związki flawonowe, takie jak wogonina, oraz polifenole, w tym kwas elagowy zawarty w whisky, brandy i koniaku [100,[115][116][117], mają udowodniony, na razie w badaniach u zwierząt doświadczalnych, ochronny wpływ wobec wrzodotwórczego działania etanolu na śluzówkę żołąd-ka [118][119][120][121]. Wykazano także korzystny efekt resweratrolu w doświadczalnym ostrym zapaleniu trzustki [122,123].…”
Section: O Wpływie Napojów Alkoholowych Na Układ Trawienny W Ujęciu Nunclassified